Understanding the NG2 Glial Scar after Spinal Cord Injury - Hackett, Amber R.; Lee, Jae K. (Frontiers in Neurology, 2016)
NG2 cells, also known as oligodendrocyte progenitor cells, are located throughout the central nervous system and serve as a pool of progenitors to differentiate into oligodendrocytes. In response to spinal cord injury, NG2 cells increase their proliferation and differentiation into remyelinating oligodendrocytes. While astrocytes are typically associated with being the major cell type in the glial scar, many NG2 cells also accumulate within the glial scar but their function remains poorly understood. Similar to astrocytes, these cells hypertrophy, upregulate expression of chondroitin sulfate proteoglycans, inhibit axon regeneration, contribute to the glial-fibrotic scar border, and some even differentiate into astrocytes. Whether NG2 cells also have a role in other astrocyte functions, such as preventing the spread of infiltrating leukocytes and expression of inflammatory cytokines, is not yet known. Thus, NG2 cells are not only important for remyelination after spinal cord injury, but are also a major component of the glial scar with functions that overlap with astrocytes in this region. In this review, we describe the signaling pathways important for the proliferation and differentiation of NG2 cells, as well as the role of NG2 cells in scar formation and tissue repair.